Law Community of “Tatar-Sunda”: Preservation of Forests and Climate Change - SUSANTO, Anthon F.; RAHAYU, Mella Ismelina.F; MULIYA, Liya Sukma (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article outlines the wisdom of the Tatar Sunda customary community in preserving the functions of forests that can contribute to climate change mitigation efforts. This paper is the result of a study that uses a sociological juridical approach method. Field studies are conducted to obtain primary data through interview and observation techniques. The results of this study explain that through the establishment of forest protection and management areas, it can be prevented forest destruction, maintain the balance and harmony of the surrounding environment slowing down the occurrence of climate change. RESUMEN Este artículo describe la sabiduría de la comunidad consuetudinaria de Tatar Sunda para preservar las funciones de los bosques que pueden contribuir a los esfuerzos de mitigación del cambio climático que se producen. Este artículo es el resultado de un estudio que utiliza un método de enfoque jurídico sociológico. Se realizan estudios de campo para obtener datos primarios a través de técnicas de entrevista y observación. Los resultados de este estudio explican que a través del establecimiento de áreas de manejo y protección forestal, puede prevenirse la destrucción del bosque, mantener el equilibrio y la armonía del ambiente circundante frenando la ocurrencia del cambio climático.